1998
DOI: 10.1148/radiology.209.3.9844680
|View full text |Cite
|
Sign up to set email alerts
|

Early renal involvement in diabetes mellitus: comparison of renal Doppler US and radioisotope evaluation of glomerular hyperfiltration.

Abstract: Both RI and renal volume showed correlation with GFR, but neither parameter is sufficiently sensitive in screening for hyperfiltration in IDDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…RI was determined as follows: the peak systolic velocity minus the end diastolic velocity divided by the peak systolic velocity. The usefulness of RI as a noninvasive hemodynamic assessment of the transplanted kidney was previously pointed out (7)(8)(9)(10). Our technique for CDU to evaluate RI is reproducible (coefficient of variation [CV], 3-5%) and precise.…”
Section: Clinical Follow-upmentioning
confidence: 92%
See 3 more Smart Citations
“…RI was determined as follows: the peak systolic velocity minus the end diastolic velocity divided by the peak systolic velocity. The usefulness of RI as a noninvasive hemodynamic assessment of the transplanted kidney was previously pointed out (7)(8)(9)(10). Our technique for CDU to evaluate RI is reproducible (coefficient of variation [CV], 3-5%) and precise.…”
Section: Clinical Follow-upmentioning
confidence: 92%
“…Initially, diabetic nephropathy encompasses both functional changes (i.e., reduced renal vasodilatory reserve and reduced ability to respond to pathogen) and slight morphological alterations (with basal membrane thickness). Finally, diabetic nephropathy results in clear morphological alterations (3,9,10).…”
Section: Preliminary Data On Nos Kidney Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrarenal RI has also found adherents as a useful marker of diabetic nephropathy (Frauchiger et al, 2000;Soldo et al, 1997). In contrast, other studies have suggested that Doppler US provides little more than serum creatinine levels and creatinine clearance rates in patients with early diabetic nephropathy and normal renal functions (Marzano et al, 1998;Okten et al, 1999;Sari et al, 1999). The intrarenal RI is significantly greater in pregnant patients with pyelonephritis than in pregnant women without pyelonephritis (Keogan et al, 1996b).…”
Section: Renal Medical Diseasesmentioning
confidence: 96%